Water mites of the genus Ljania Thor, 1898 (Acari: Hydrachnidia: Aturidae) in Russia - Tuzovskij, Petr V. (Zootaxa, 2012)
This study presents a detailed taxonomic review of water mites of the genus Ljania Thor, 1898 (Aturidae, Axonopsinae)found in the fauna of Russia. The review includes illustrations and (re)description of males and females of three species:L. bipapillata Thor, 1898, L. macilenta Koenike, 1908 and L. orientalis sp. n. A diagnosis of the genus Ljania and identification key to the listed species based on adults are given.